The intervention strategies and service model for pharmacist-led diabetes management: a scoping review - Fahmi Hassan; Ernieda Hatah; Adliah Mhd Ali; Chong Wei Wen (BMC, 2023)
Abstract Background There is increasing intervention activities provided during pharmacist-led diabetes management. Nevertheless, there is an unclear definition of the activities involved during the intervention. Thus, this study aimed to describe the type of intervention strategies and service model provided during pharmacist-led type 2 diabetes management and service outcomes. Methods This study utilized the scoping review methodology of the Joanna Briggs Institute Reviewers' Manual 2015. Articles on pharmacist-led diabetes management focusing on the service content, delivery methods, settings, frequency of appointments, collaborative work with other healthcare providers, and reported outcomes were searched and identified from four electronic databases: Ovid Medline, PubMed, Scopus, and Web of Science from 1990 to October 2020. Relevant medical subject headings and keywords, such as "diabetes," "medication adherence," "blood glucose," "HbA1c," and "pharmacist," were used to identify published articles. Results The systematic search retrieved 4,370 articles, of which 61 articles met the inclusion criteria. The types of intervention strategies and delivery methods were identified from the studies based on the description of activities reported in the articles and were tabulated in a summary table. Conclusion There were variations in the descriptions of intervention strategies, which could be classified into diabetes education, medication review, drug consultation/counseling, clinical intervention, lifestyle adjustment, self-care, peer support, and behavioral intervention. In addition, most studies used a combination of two or more intervention strategy categories when providing services, with no specific pattern between the service model and patient outcomes.